Sex and pressure effects of foam rolling on acute range of motion in the hamstring muscles - Norikazu Hirose; Akane Yoshimura; Kei Akiyama; Atsuya Furusho (PLoS ONE, 2025)
This study investigated the effects of pressure levels and sex on acute range of motion (ROM) changes during foam rolling (FR) using a soccer ball. Twenty collegiate athletes (10 males, 10 females) performed FR on their hamstrings at low (15–25% body weight) or high (45–55%) pressure levels for 2 minutes. ROM was assessed through passive straight leg raise (PSLR) and passive knee extension (PKE) tests before, immediately after, and 10 minutes post-intervention. Results showed that FR significantly improved hip and knee ROM across all conditions, with benefits persisting for at least 10 minutes. No notable differences were observed between pressure levels, and sex did not affect the magnitude of improvement. Perceived pain during FR did not significantly influence ROM outcomes. These findings demonstrate that FR using a simple tool like a soccer ball is beneficial for improving ROM in both males and females, regardless of pressure intensity. This suggests that FR provides a practical, accessible method for improving ROM in athletes and other populations.